Indigenous records: connecting, critiquing and diversifying collections - Kirsten Thorpe (Archives & Manuscripts, 2014)
The management of Indigenous records and collections presents challenges to traditional archival methods and practice. Indigenous issues relating to the management of archives are important questions that should be discussed and considered broadly by the profession. In this paper, I will draw on my own professional and personal experiences of working as an Indigenous archivist to illustrate some of these challenges.